Penguatan Personal Branding Mahasiswa Universitas Negeri Makassar melalui Optimalisasi Media Sosial - Ilma Wulansari Hasdiansa; Sitti Hasbiah; Nurul Fadilah Aswar; Isma Azis Riu; Deddy Ibrahim Rauf (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Social media has become the main platform for university students to express themselves and build professional reputation. However, many students have not yet been able to utilize social media positively to support their academic and career growth. This community service aimed to strengthen students’ understanding and skills in developing personal branding through effective social media utilization. The program was implemented through workshops, discussions, and mentoring for students of the Faculty of Economics and Business, Universitas Negeri Makassar. Pre-test and post-test evaluations were conducted to assess participants’ knowledge improvement. The students’ average score increased, indicating significant improvement. Majority of participants began applying personal branding strategies on their social media accounts. The activity effectively enhanced students’ awareness and ability to build professional online identities.